ANALISIS AL-MADZHAB AL-KALAMI DALAM SURAH AL-QIYAMAH DAN HUSN AL-TA’LIL DALAM SURAH AL-ZARIYAH - Aqila, Aqila; Hasibuan, Ernida; Al Ghozi, Haidarul Ghalib; Al Rasyid, Harun (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
This study aims to analyze Al-Madzhab Al-Kalami and Husn At-Ta'lil in Surah Al-Qiyamah and Az-Zariyat, as part of the study of the beauty of the Qur'anic language in the science of balaghah. The method used is a qualitative approach with literature studies, in order to ensure the validity of the data and produce findings that can be a reference in further studies. The research findings show that in Surah Al-Qiyamah, Al-Madzhab Al-Kalami appears mostly in the form of claims preceded by more than two muqaddimah (premises), to strengthen the delivery of the truth message contained therein. Whereas in Surah Az-Zariyat, Husn At-Ta'lil is used by giving beautiful and clear reasons to emphasize the meaning and direct the reader to a deep reflection on the greatness of Allah. These two forms show the uniqueness of the Qur'anic language structure that not only conveys meaning, but also builds logical arguments and language aesthetics in harmony.